When East Meets West: A Needs Analysis of Foreign Language Learning (Français) in The Philippines - Alberto-Pedida, Jefferson Alberto-Pedida (CV. Literasi Indonesia, 2024)
With a focus on education and language learning in the context of the Philippines, this paper explores the blending of Western and Eastern cultures. The exploration narrows down to Isabela State University, where the study conducts a needs analysis of French language education. To identify the difficulties faced by French learners such as pronunciation problems, grammatical errors, and the limitations of traditional teaching methods the method combines questionnaires and interviews with a qualitative-descriptive design. The study highlights how crucial it is to understand students' needs, explore their difficulties, and offer suggestions for curriculum-related improvements that pinpoint important factors needed for learning French. The findings show that students struggled with a variety of linguistic competencies. Teachers are aware of the need for more comprehensive teaching materials for students, especially when it comes to grammar and pronunciation. Thus, the suggestions for material enhancements revolve around liaison, homophones, writing rules, as well as promoting conversational French. The analysis emphasizes how essential it is to implement a thorough plan that addresses the four macro skills of speaking, listening, reading, and writing. In a nutshell, the study adds to the larger discussion about the significance of foreign language education in a global setting by shedding light on the issues faced by French language learners at Isabela State University and offering specific recommendations for curriculum development and teaching materials.